Dynamic vascular changes in chronic thromboembolic pulmonary hypertension after pulmonary endarterectomy. (1st October 2020) - Ruigrok, Dieuwertje; Braams, Natalia J.; Nossent, Esther J.; Bonta, Peter I.; Boonstra, Anco; Lely, Rutger J.; Klok, Frederikus A.; Vonk Noordegraaf, Anton; Symersky, Petr; Bogaard, Harm‐Jan; Meijboom, Lilian J.
Abstract : Residual pulmonary hypertension is an important sequela after pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension. Recurrent thrombosis or embolism could be a contributor to this residual pulmonary hypertension but the potential extent of its role is unknown in part because data on incidence are lacking. We aimed to analyze the incidence of new intravascular abnormalities after pulmonary endarterectomy and determine hemodynamic and functional implications. A total of 33 chronic thromboembolic pulmonary hypertension patients underwent routine CT pulmonary angiography before and six months after pulmonary endarterectomy, together with right heart catheterization and exercise testing. New vascular lesions were defined as (1) a normal pulmonary artery before pulmonary endarterectomy and containing a thrombus, web, or early tapering six months after pulmonary endarterectomy or (2) a pulmonary artery already containing thrombus, web, or early tapering at baseline, but increasing six months after pulmonary endarterectomy. Nine of 33 (27%) chronic thromboembolic pulmonary hypertension patients showed new vascular lesions on CT pulmonary angiography six months after pulmonary endarterectomy. In a subgroup of patients undergoing CT pulmonary angiography 18 months after pulmonary endarterectomy, no further changes in lesions were noted. Hemodynamic and functional outcomes were not different between patients with and without new vascular lesions. New vascular lesions are common after pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension; currently their origin, dynamics, and long‐term consequences remain unknown.